Skip to main content
\(\require{cancel}\)
Physics LibreTexts

6.1: Useful formulas

  • Page ID
    31978
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    \(A=a_{0} 1+\vec{a} \cdot \vec{\sigma} \tilde{A}=a_{0} 1-\vec{a} \cdot \vec{\sigma} A^{\dagger}=a_{0}^{*} 1+\vec{a}^{*} \cdot \vec{\sigma} \bar{A}=\tilde{A}^{\dagger}=a_{0}^{*} 1-\vec{a}^{*} \cdot \vec{\sigma}\)

    \[\frac{1}{2} \operatorname{Tr}(A)=a_{0}, \quad|A|=a_{0}^{2}-\vec{a}^{2} 1 \frac{1}{2} \operatorname{Tr}(A \tilde{A})\label{1}\]

    \[\frac{1}{2} \operatorname{Tr}(A \tilde{B})=a_{0} b_{0}-\vec{a} \cdot \vec{b}\label{2}\]

    \[A^{-1}=\frac{\tilde{A}}{|A|} \quad \text { for } \quad|A|=1: A^{-1}=\tilde{A}\label{3}\]

    \[(\vec{a} \cdot \vec{\sigma})(\vec{b} \cdot \vec{\sigma})=\vec{a} \cdot \vec{b} 1+i(\vec{a} \times \vec{b}) \cdot \vec{\sigma}\label{4}\]

    \[\text { For } \vec{a} \| \vec{b} \quad \frac{a_{1}}{b_{1}}=\frac{a_{2}}{b_{2}}=\frac{a_{3}}{b_{3}} \quad \vec{a} \times \vec{b}=0\label{5}\]

    \[(\vec{a} \cdot \vec{\sigma})(\vec{b} \cdot \vec{\sigma})-(\vec{b} \cdot \vec{\sigma})(\vec{a} \cdot \vec{\sigma})=[(\vec{a} \cdot \vec{\sigma}),(\vec{b} \cdot \vec{\sigma})]=0\label{6}\]

    \[\text { For } \quad A=a_{0} 1+\vec{a} \cdot \vec{\sigma}, \quad B=b_{0} 1+\vec{b} \cdot \vec{\sigma}\label{7}\]

    \[[A, B]=0 \quad \text { iff } \quad \vec{a} \| \vec{b}\label{8}\]

    \[\begin{equation}
    \begin{array}{ll}
    \text { For } \quad & \vec{a} \perp \vec{b}, \quad \vec{a} \cdot \vec{b} \\
    & \{\vec{a} \cdot \vec{\sigma}, \vec{b} \cdot \vec{\sigma}\} \quad \equiv \quad(\vec{a} \cdot \vec{\sigma})(\vec{b} \cdot \vec{\sigma})+(\vec{b} \cdot \vec{\sigma})(\vec{a} \cdot \vec{\sigma})=0
    \end{array}
    \end{equation}\label{9}\]

    \[A(\vec{b} \cdot \vec{\sigma})=(\vec{b} \cdot \vec{\sigma}) \tilde{A}\label{10}\]

    \[U=U\left(\hat{u}, \frac{\phi}{2}\right)=\cos \frac{\phi}{2} 1-i \sin \frac{\phi}{2} \hat{n} \cdot \vec{\sigma}=\exp \left(-i \frac{\phi}{2} \hat{n} \cdot \vec{\sigma}\right)\label{11}\]

    \[H=H\left(\hat{h}, \frac{\mu}{2}\right)=\cosh \frac{\mu}{2} 1+\sinh \frac{\mu}{2} \hat{h} \cdot \vec{\sigma}=\exp \left(\frac{\mu}{2} \hat{h} \cdot \vec{\sigma}\right)\label{12}\]

    \(U\) unitary unimodular, H Hermitian and positive.


    6.1: Useful formulas is shared under a CC BY-NC-SA license and was authored, remixed, and/or curated by László Tisza (MIT OpenCourseWare) .

    • Was this article helpful?